Laboratory and field evaluation of Metarhizium anisopliae var. anisopliae for controlling subterranean termites - Hussain,A (2011)
The efficacy of the Metarhizium anisopliae strain ARSEF 6911 was determined in the laboratory and field against two sugarcane pests, Microtermes obesi Holmgren and Odontotermes obesus Rambur (Termitidae: Isoptera). The susceptibility of both termite species to different conidial suspensions (1 × 10(10), 1 × 10(8), 1 × 10(6) and 1 × 10(4) conidia/ml) was determined in laboratory. All conidial suspensions were able to induce mortality. Termite mortality caused by the fungal suspensions was dose dependent. There were no significant differences in the LT50 values between species. Field evaluation of M. anisopliae alone or in combination with diesel oil and thiamethoxam was carried out in two growing seasons (autumn 2005 and spring 2006) at two sites located in Punjab, Pakistan. Dipping the sugarcane setts in these suspensions was tried to determine their effects on germination and percentage of bud damage to sugarcane setts. All treatments significantly reduced termite infestation compared to the untreated control. The combined treatment of M. anisopliae and diesel oil significantly reduced insect damage by attaining higher germination > 55% and lower bud damage < 5.50% at both sites in both seasons. The results suggest that the application of M. anisopliae and diesel oil in combination might be a useful treatment option for the management of termites in sugarcane.